Analysis of Strategies To Increase The Income of Fish Processing Businesses Through The Diversification of Processed Fish Products - Dinda, Mita; Dewi, Yenty Astarie; Nurani, Khadijah; Putra, Indika Juang (International Journal of Education, Information Technology, and Others, 2025)
This study aims to analyze income improvement strategies through diversification, covering aspects of capital conditions, technology, seasonal impacts, and strategy formulation. Method: Descriptive qualitative approach using observation and interviews with six informants, thematic analysis, and secondary data from BPS and KKP (2022–2024). The study employs a descriptive qualitative approach through observation and interviews with six informants, thematic analysis, and secondary data from BPS and KKP (2022–2024). Results show that the number of actors increased by 50%, production rose by 100%, and income grew by 84% (from IDR 44.1 million to IDR 54.2 million). Challenges: Seasonal fluctuations and limited diversification, with interest in products such as fish floss. Conclusion: Diversification supported by modern technology, sharia-based financing, and digital marketing can.